Planning your kitchen - Manser, José.; Manser, Michael (London, United Kingdom : Design Council, 1976)
This book is a design centre book. The series aims to provide he consumer with practical advice on equipping and planning the home, and there will also be titles covering special aspects of design and planning.
Introduction -- Personal needs -- Different shapes and sizes -- Equipment -- Storage -- Technicalities -- Safety in the kitchen -- Decorations -- Kitchens in the future -- Index.
Includes index.
Keywords: KITCHEN -- STYLES